THE BOOMERANG EXPERIMENT - LANGE, A; DEBERNARDIS, P; DE PETRIS, M; MASI, S; MELCHIORRI, F; AQUILINI, E; MARTINIS, L; SCARAMUZZI, F; MELCHIORRI, B; BOSCALERI, A; ROMEO, G; BOCK, J; et al. (Space Science Reviews, 1995)
The BOOMERANG (Balloon Observations Of Millimetric Extragalactic Radiation aNd Geophysics) experiment is an international effort to measure the Cosmic Microwave Background (CMB) anisotropy on angular scales of 20' to 40 degrees, with unprecedented sensitivity, sky and spectral coverage. The telescope will be flown from Antarctica by NASA-NSBF with a long duration stratospheric balloon (7-14 days), and is presently scheduled for flight in 1995-1996. The experiment is designed to produce an image of the Cosmic Microwave Background with high sensitivity and large sky coverage. These data will tightly constrain the baryon density, the reionization history, and the formation of large-scale structure in the universe. BOOMERANG will test technologies and return science data that are essential to the design of a future space-borne mission to map CMB anisotropy.